1999
DOI: 10.1007/s004110050143
|View full text |Cite
|
Sign up to set email alerts
|

The Bethe surface of liquid water

Abstract: The Bethe surface of liquid water, earlier calculated using a semi-empirical model, is compared with recent available data from IXS-experiments (inelastic X-ray scattering; Compton scattering of high energy photons) in liquid water. No alarming discrepancy is found on a global view of the Bethe surface. The extrapolation to the optical limit (viz., at zero momentum transfer) is shown and the reliability of these data is discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 5 publications
(12 reference statements)
2
14
0
Order By: Relevance
“…3 have been obtained using the truncated maximum energy-transfer value given by Eq. (33). We should note that unless we go to very low energies, the Fermi cut-off condition, E max ¼ T -E F , is inconsequential since it is always higher than the truncated condition E max ¼ (1/2)(T þ E min ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…3 have been obtained using the truncated maximum energy-transfer value given by Eq. (33). We should note that unless we go to very low energies, the Fermi cut-off condition, E max ¼ T -E F , is inconsequential since it is always higher than the truncated condition E max ¼ (1/2)(T þ E min ).…”
Section: Resultsmentioning
confidence: 96%
“…This class of models, often quoted as the ''extended-Drude scheme'' or, simply, ''the Ritchie scheme'', was later refined and improved by Dingfelder and others (32)(33)(34) who, among other things, treated binding effects in the dielectric function in a consistent manner. The theoretical basis of the extended-Drude model is a generalization of the plasmon-pole approximation of the Lindhard dielectric function (35).…”
mentioning
confidence: 98%
“…The Bethe surface of liquid water as determined experimentally by IXS measurements [18,45] and calculated by different extended-optical-data dielectric models (see text). duced by any type of energy-dispersion relation alone and some type of a damping-dispersion also needs to be invoked [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…More details of the calculations may be found in Emfietzoglou et al (2008). with the dielectric model of Dingfelder et al (1998) revealed that whereas the general features were reproduced by the model, the experimental Bethe ridge was much broader and less intense (Dingfelder and Inokuti, 1999).…”
Section: Recent Advancementsmentioning
confidence: 93%